2021
DOI: 10.1155/2021/1828145
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Crumb Rubber with a Silane Coupling Agent to Improve Asphalt Rubber Performance

Abstract: There are known problems of dissolution, consistency of performance, segregation, and instability with the crumb rubber currently used in asphalt for road engineering. A silane coupling agent (KH550) solution was therefore used to pretreat the crumb rubber so as to improve its interfacial characteristics. The effects of KH550 on the properties of asphalt rubber were studied using high- and low-temperature performance tests, temperature sensitivity test, and compatibility test. On the basis of these tests, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…As the number of vehicles on the road grows, so does the number of tires. According to estimates, around the globe billions of tires are produced each year, the most of which will end up as waste tires (Chen et al, 2020;Liu et al, 2021). To keep up with the increased volume of traffic, asphalt concrete must evolve as well in order to improve the material's resistance to rutting and cracking and also increase its durability (Wiranata & Malik, 2021).…”
Section: Overview Of Asphalt Rubber (Ar)mentioning
confidence: 99%
See 2 more Smart Citations
“…As the number of vehicles on the road grows, so does the number of tires. According to estimates, around the globe billions of tires are produced each year, the most of which will end up as waste tires (Chen et al, 2020;Liu et al, 2021). To keep up with the increased volume of traffic, asphalt concrete must evolve as well in order to improve the material's resistance to rutting and cracking and also increase its durability (Wiranata & Malik, 2021).…”
Section: Overview Of Asphalt Rubber (Ar)mentioning
confidence: 99%
“…Ground Tire Rubber (GTR) or Crumb Rubber (CR), which has been utilized in the paving industry since the 1960s, is one way of recycling scrap tires. Since then, it has grown in popularity around the world as a solution to a severe waste management problem and an improvement in asphalt surface performance (Chang et al, 2020;Liu et al, 2021). No matter how much tire composition differs from one manufacturer to another and from one type of vehicle to another, the primary components of all tires are nearly identical.…”
Section: Overview Of Asphalt Rubber (Ar)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, chemical activation has good application prospects because of its high reaction efficiency and low energy consumption. Studies have shown that H 2 O 2 , the silane-coupling agent, and ethylene vinyl acetate can increase the solubility of crumb rubber in asphalt [11][12][13]. Ren [14,15] analyzed the influence of the expansion-degradation degree of crumb rubber in asphalt on the chemical and rheological properties of rubber asphalt, and considered that the degradation of crumb rubber increased the formation of free hydroxide groups.…”
Section: Introductionmentioning
confidence: 99%